Attentional Bias to Beauty with Evolutionary Benefits: Evidence from Aesthetic Appraisal of Landscape Architecture - Zhang, Wei; Tang, Xiaoxiang; He, Xianyou; Lai, Shuxian (Frontiers in Psychology, 2018)
Substantial evidence suggests that beauty is associated with the survival and reproduction of organisms. Landscape architecture is composed of a series of natural elements that have significant evolutionary implications. The present study used 4 experiments to examine the mechanisms of aesthetic appraisals of landscape architecture. The results confirmed that landscape architecture elicited a sense of beauty and captured visual attention more easily than other types of architecture during explicit aesthetic rating task (Experiment 1) and implicit aesthetic perception task (dot-probe paradigm, Experiment 2). Furthermore, the spatial cueing paradigm revealed that response latencies were significantly faster for landscape architecture than non-landscape architecture on valid trials, but there was no significant difference in this contrast on invalid trials at 150-ms stimulus onset asynchrony (SOA, Experiment 3a). At 500-ms SOA (Experiment 3b), participants responded significantly faster for landscape architecture on valid trials, but reacted significantly slower for landscape architecture on invalid trials. The findings indicated that the beauty of landscape architecture can be perceived implicitly, and only faster orienting of attention, but not delayed disengagement of attention was generated at early stages of the processing of landscape architecture. However, the attentional bias at later stages of attentional processes may be resulted from both faster orienting of attention and delayed disengagement of attention from landscape architecture photographs.